A global portrait of counselling psychologists' characteristics, perspectives, and professional behaviors. Issue 2 (2nd April 2016) - Goodyear, Rod; Lichtenberg, James; Hutman, Heidi; Overland, Emily; Bedi, Robinder; Christiani, Kayla; Di Mattia, Michael; du Preez, Elizabeth; Farrell, Bill; Feather, Jacqueline; Grant, Jan; Han, Young-joo; et al.
Abstract : Counseling psychologists in eight countries (Australia, Canada, New Zealand, South Africa, South Korea, Taiwan, the United Kingdom, and the United States) responded to survey questions that focused on their demographics as well as their professional identities, roles, settings, and activities. As well, they were asked about satisfaction with the specialty and the extent to which they endorsed 10 core counseling psychology values. This article reports those results, focusing both on areas in which there were between-country similarities as well as on those for which there were differences. These data provide a snapshot of counseling psychology globally and establish a foundation for the other articles in this special issue of the journal.